Public sector pay and corruption: measuring bribery from micro data - Yuriy Gorodnichenko; Klara Sabirianova Peter (Institute for the Study of Labor (IZA), 2006)
This study is the first to provide a systematic measure of bribery using micro-level data on reported earnings, household spending and asset holdings. We use the compensating differential framework and the estimated sectoral gap in reported earnings and expenditures to identify the size of unobserved (unofficial) compensation (i.e., bribes) of public sector employees. In the case of Ukraine, we find that public sector employees receive 24-32% less wages than their private sector counterparts. The gap is particularly large at the top of the wage distribution. At the same time, workers in both sectors have essentially identical level of consumer expenditures and asset holdings that unambiguously indicate the presence of non-reported compensation in the public sector. Using the conditions of labor market equilibrium, we develop an aggregate measure of bribery and find that the lower bound estimate of the extent of bribery in Ukraine is between 460 mln and 580 mln U.S. dollars (0.9-1.2% of Ukraine's GDP in 2003).
Keywords: J3; J4; O1; P2; 330; wage; wage differentials; public sector; corruption; bribery; Ukraine; Öffentlicher Dienst; Gehalt; Vergleich; Privatwirtschaft; Korruption; Ukraine; Öffentlicher Dienst; Gehalt; Vergleich; Privatwirtschaft; Korruption; Ukraine